Distinctive Modulatory Effects of Five Human Auxiliary β(2) Subunit Splice Variants on L-Type Calcium Channel Gating - Takahashi, Shoji X. (Biophysical Society, 2003)
Sequence analysis of the human genome permitted cloning of five Ca(2+)-channel β(2) splice variants (β(2a)–β(2e)) that differed only in their proximal amino-termini. The functional consequences of such β(2)-subunit diversity were explored in recombinant L-type channels reconstituted in HEK 293 cells. β(2a) and β(2e) targeted autonomously to the plasma membrane, whereas β(2b)–β(2d) localized to the cytosol when expressed in HEK 293 cells. The pattern of modulation of L-type channel voltage-dependent inactivation gating correlated with the subcellular localization of the component β(2) variant—membrane-bound β(2a) and β(2e) subunits conferred slow(er) channel inactivation kinetics and displayed a smaller fraction of channels recovering from inactivation with fast kinetics, compared to β(2b)–β(2d) channels. The varying effects of β(2) subunits on inactivation gating were accounted for by a quantitative model in which L-type channels reversibly distributed between fast and slow forms of voltage-dependent inactivation—membrane-bound β(2) subunits substantially decreased the steady-state fraction of fast inactivating channels. Finally, the β(2) variants also had distinctive effects on L-type channel steady-state activation gating, as revealed by differences in the waveforms of tail-activation (G-V) curves, and conferred differing degrees of prepulse facilitation to the channel. Our results predict important physiological consequences arising from subtle changes in Ca(2+)-channel β(2)-subunit structure due to alternative splicing and emphasize the utility of splice variants in probing structure-function mechanisms.